Ideation and Design Ability as Antecedents for Design Expertise. Issue 4 (1st October 2020) - Casakin, Hernan; Levy, Shalom
ABSTRACT: The question of how individual features affect the development of design expertise has yet to be thoroughly researched. While some works acknowledged the importance of design abilities and creative ideation for design expertise, there is no theoretical framework that explicates their relationships and supports it empirically. The present research proposes a conceptual model and examines these relationships while integrating temporal experience as a moderating factor. Data were collected using a survey distributed among web community groups of designers and analyzed using Structural Equation Modeling (SEM). Findings showed that design ability was positively related to design expertise, and design creative ideation was positively related to design ability. Moreover, the positive relationship between design creative ideation and design expertise was mediated by design ability. Additionally, design experience moderated the relationship between design ideation and design ability, indicating that the relationship between ideation and design ability was stronger for less experienced designers. This study facilitates a deeper understanding about the contribution of design ability, creative ideation, and temporal experience to design expertise.